Differences in training characteristics of recreational endurance runners by race distance – results from the NURMI Study (Step 2) - Knechtle, Beat; Tanous, Derrick; Thuany, Mabliny; Motevalli, Mohamad; Wirnitzer, Gerold; Leitzmann, Claus; Weiss, Katja; Rosemann, Thomas; Wirnitzer, Katharina (Frontiers in Psychology, 2024)
Background: Although runner’s profiles were previously investigated, information on the training frequency and training distance for short (5km, 10km) and long-distance (>21km) running is absent. The present study aimed to investigate the associations between training routines and exercise habits of recreational endurance runners considering self-reported preferred race distance (10 km, half-marathon (HM), and marathon/ultra-marathon (M/UM)) subgroups. Methods: This is a cross-sectional study, sampling 154 recreational runners of both sexes. A web survey was used for data collection regarding age, sex, preferred distance (10-km, HM, M/UM), training routines, exercise habits, and periodized training routines. The Chi-square test (Cramer’s V) and Kruskal-Wallis test (Eta-Squared η2) with effect sizes were used for comparisons between race distances. Results: Significant differences were shown for anthropometric, training, and periodization characteristics. Highly significant differences were found between subgroups for the number of sessions, running kilometers, and training hours at all periods and within all four preparation conditions. M/UM runners were training more frequently, for longer durations, and ran greater distances each week. Conclusion: This finding supports the notion that training habits and periodization characteristics are different for different race distances (10-km, half marathon, marathon, and ultramarathon).